Proceedings of the 7th International Conference on Kansei Engineering and Emotion Research 2018 KEER 2018, 19-22 March 2018, Kuching, Sarawak, Malaysia - Lokman, Anitawati Mohd.; Yamanaka, Toshimasa; Lévy, Pierre; Chen, Kuohsiang; Koyama, Shinichi; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2018)
The proceedings gather a selection of refereed papers presented at the 7th International Conference on Kansei Engineering and Emotion Research 2018 (KEER 2018), which was held in Kuching, Malaysia from 19 to 22 March 2018. The contributions address the latest advances in and innovative applications of Kansei Engineering and Emotion Research. The subjects include: Kansei, Emotion and Games Kansei, Emotion and Computing Kansei, Emotion and Wellbeing / Quality of Life Kansei, Emotion and Design Kansei, Emotion and Health / Ergonomics Kansei, Emotion and Multidisciplinary Fields Kansei, Emotion and Culture Kansei, Emotion and Social computing Kansei, Emotion and Evaluation Kansei, Emotion and User Experience The book offers a valuable resource for all graduate students, experienced researchers and industrial practitioners interested in the fields of user experience/usability, engineering design, human factors, quality management, product development and design.
Part 1: Kansei, Emotion, and Games -- chapter 1. A Fundamental Study of a Computer Player Giving Fun to the Opponent -Targeting Hanafuda, a Card Game in Japan -- chapter 2. Exploring the Critical Appeal of Mobility-Augmented Reality Games -- chapter 3. Interactive Games Effects on Children's Affective Cooperation: Evaluating Cooperation Through Kansei-Based Play and Design Sections -- chapter 4. Kansei Engineering Approach in Designing Appealing Computer Animation Character -- chapter 5. The Content and Design of Art Museum On-line Learning Games for Children -- chapter 6. Understanding of User's Gameplay Behavior and Perception Styles in an Environment of Digital Gesture Based-Game -- Part 2: Kansei, Emotion and Computing -- chapter 7. A Smart Home Model Using Android Application -- chapter 8. A State of Art on Kansei-Engineered Virtual Shops: A Study on the Possibilities of V-Commerce -- chapter 9. A System Analysis and Design for SMEs Product Presentation in Ecommerce Website Based on Kansei Engineering (Case Study: SMEs Products of Ponorogo Regency) -- chapter 10. Accuracy of Geolocation Data of Taman Wetland Putrajaya -- chapter 11. Brand Name Decision AI System -- chapter 12. Development of Virtual Draping System by Augmented Reality -- chapter 12. Just in Mobile Augmented Reality Technology (JIMART) Application -- chapter 13. Virtual Agent Design Factors for the 21St Century Learners: A Kansei Approach -- Part 3: Kansei, Emotion and Wellbeing / Quality of Life -- chapter 14. Conceptualization of Happiness Index Model -- chapter 15. Factorization of Accomplishment Domain of PERMAI Model -- chapter 16. From PERMA to PERMAIg©: Happiness Instrument Development -- chapter 16. Happiness Index Measurement: Application of Kansei Engineering and Positive Psychology -- chapter 17. Measuring Employee Happiness: Analyzing the Dimensionality of Employee Engagement -- chapter 18. Modeling Factors and Importance of Happiness Using KJ Method -- chapter 19. Relationship Between Workers' GeneralHappiness and Emotional Components @ PERMAIg© -- chapter 20. Reliability of Happiness Index Model Questionnaire -- chapter 21. Visual Analytics of Happiness Index in Parallel Coordinate Graph -- Part 4: Kansei, Emotion and Design -- chapter 22. A Study for Application of Color Design in Product Design of Woodworking Machine Tooltitle.
Keywords: Engineering design; Industrial Management; Customer relations -- Management; Manufactures; Emotions; Cognitive psychology; Engineering Design; Industrial Management; Customer Relationship Management; Machines, Tools, Processes; Emotion; Cognitive Psychology